The Valuation of Organizational Capital - Fiala Roman, Borůvková Jana; Borůvková Jana (Journal of Competitiveness, 2012)
The authors’ aim was to create a model suitable for measuring organization capital. This model was produced by means of the Forward and Backward Stepwise methods, on the basis of company information. Low p-levels (approaching 0) show the statistical significance of all regression coefficients, including the intercept. Organizational capital of 2,796 companies in the Czech Republic was quantified. A statistically significant correlation between organizational capital and return on equity (ROE), as well as between organizational capital and return on assets (ROA), has been established. This article is a part of the results of the project No. 402/09/2057 ‘‘Measurement and Management of Intangible Assets Impact on Firm Performance’’ financed by Czech Science Foundation.